INTERAKSI SOSIAL ANTAR ETNIS MELAYU DENGAN DAYAK DI DESA BALAI BERKUAK KECAMATAN SIMPANG HULU KABUPATEN KETAPANG - Marodama, Eskiel; Bahari, Yohanes; Salim, Izhar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract :The purpose of this research is to This study entitled Social interaction between ethnic Melayu and Dayak in Balai Berkuak village, Simpang Hulu District, Ketapang Regency. With the problem of how the form of cooperation, accommodation and forms of community competition between ethnic Melayu and Dayak. This research method is a descriptive qualitative approach. The data source of this research is primary data and secondary data. The results of the study show that: Spontaneous cooperation that is shown by mutual assistance when there are residents who experience a disaster, regardless of status, direct cooperation, namely cooperation carried out by the community on orders or socialization from the RT or Village Head. Accommodation, tolerance is maintained both among Dayak and Melayu. It is considered the same because good actions are not seen from the tribe but by the nature or character of a person. Individual competition looks normal and is said to be good, group competition, still a bit in the economic and sports fields can be said to be good and positive.Keywords: Social Interaction,Ethnic, Melayu, Dayak.